2016
DOI: 10.1123/japa.2015-0146
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Depressive Symptoms in Older Adults: A Systematic Meta-Analytic Review

Abstract: Depressive symptoms are common in older adults, but antidepressant medications may be contraindicated or poorly tolerated in this population. Intervention studies demonstrate that exercise may be an effective alternative. This meta-analysis included 41 randomized controlled trials of aerobic and nonaerobic exercise interventions investigating the effect of exercise on depressive symptoms in adults aged 60 or older. A random effects model demonstrated that exercise was associated with significantly lower depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 0 publications
3
52
0
4
Order By: Relevance
“…Exercise had fairly robust effect sizes for risk of depression in prospective studies, and this finding is consistent with previous studies that demonstrated a significant decline in depressive symptoms after participants received interventions offering exercise support (Arent et al, 2000; Rhyner & Watts, 2016). This benefit of improving exercise might occur via different mechanisms, such as reducing the risk of experiencing diabetes complications (Lin et al, 2010), improving the immune system (Swift et al, 2012) and significant physiological metrics (e.g., A1C, or glycated hemoglobin; Macdonald, Philp, Harrison, Bone, & Watt, 2006; P. T. Williams, 2008), or even through neurotransmitters believed to be shared between exercise and depressive symptoms (Rethorst, Landers, Nagoshi, & Ross, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Exercise had fairly robust effect sizes for risk of depression in prospective studies, and this finding is consistent with previous studies that demonstrated a significant decline in depressive symptoms after participants received interventions offering exercise support (Arent et al, 2000; Rhyner & Watts, 2016). This benefit of improving exercise might occur via different mechanisms, such as reducing the risk of experiencing diabetes complications (Lin et al, 2010), improving the immune system (Swift et al, 2012) and significant physiological metrics (e.g., A1C, or glycated hemoglobin; Macdonald, Philp, Harrison, Bone, & Watt, 2006; P. T. Williams, 2008), or even through neurotransmitters believed to be shared between exercise and depressive symptoms (Rethorst, Landers, Nagoshi, & Ross, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…There is now a robust empirical evidence that engagement in PA can improve mental wellbeing of older adults [6,7,57,58] and indeed reduce symptoms [59] and prevent recurrence of depression [60]. In our review interventions generally seemed to lead to improved self-efficacy but there was less consistency in their impact on the quality of life and mood-related outcomes.…”
Section: Discussionmentioning
confidence: 88%
“…It is plausible that low HGS may serve as proxy for low exercise levels. A recent metaanalysis of 41 randomized controlled trials confirmed the effectiveness of exercise as a treatment option for depression, irrespective of age . Similarly, the implementation of exercise programs for older people has recently been shown to have a positive influence not only on mood, but also on global cognitive function and frailty status .…”
Section: Discussionmentioning
confidence: 97%